2010
DOI: 10.4314/ajbr.v11i1.50666
|View full text |Cite
|
Sign up to set email alerts
|

The effects of controlled intake of selected protein foods on nephrectomized rats

Abstract: Dietary management of patients with chronic renal failure (CRF) has remained a very tasking one, especially as it affects the source and quantity of protein in diets. This study was carried out to determine the effects of lowprotein diets from common protein foods on 36 ⅔-nephrectomized albino rats (NR). NR were placed on isocaloric 14% protein diets incorporating cooked beef (A), smoked catfish (B), cooked beef and smoked catfish (C), cooked beef, smoked catfish and sun-dried, hulled, red cowpeas (D), cooked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Using data from the Singapore Chinese Health Study to complete a substitution analysis, Lew et al estimated that the risk for developing ESRD can be reduced by substituting one serving of red meat with either one serving of poultry (62%), fish (49%), soy and/or legumes (50%) or eggs (45%) [32]. Some insight into future research in patients may be drawn from an animal model study, where Fadupin et al (2008) showed egg white and fish protein were superior to other protein sources in providing beneficial effects on food intake, anthropometric parameters, blood urea and creatinine levels in nephrectomized rats [99].…”
Section: Egg Intake and Risk Of Developing Ckdmentioning
confidence: 99%
“…Using data from the Singapore Chinese Health Study to complete a substitution analysis, Lew et al estimated that the risk for developing ESRD can be reduced by substituting one serving of red meat with either one serving of poultry (62%), fish (49%), soy and/or legumes (50%) or eggs (45%) [32]. Some insight into future research in patients may be drawn from an animal model study, where Fadupin et al (2008) showed egg white and fish protein were superior to other protein sources in providing beneficial effects on food intake, anthropometric parameters, blood urea and creatinine levels in nephrectomized rats [99].…”
Section: Egg Intake and Risk Of Developing Ckdmentioning
confidence: 99%